Resilience and Adaptation Impact of Covid-19 on Female Entrepreneurship and Motivation in Gaziantep-Türkiye - Ayda Bakan; Tuba Büyükbeşe; Emel Topcu (Journal of Economy Culture and Society)
This study aims to thoroughly investigate the effects of the COVID-19 pandemic on the domestic obligations and commercial ventures of female entrepreneurs in Türkiye. Furthermore, this research aims to examine the motivational variables that propel these women at various stages of entrepreneurship: before, during, and after the pandemic. The study used a qualitative case study methodology involving in-depth, semi-structured interviewswithasampleof25femaleentrepreneurs.Thedataanalysisentails using MAXQDA2020 software in conjunction with hermeneutic analysis. The investigation reveals a significant surge in domestic responsibilities for entrepreneurs during the pandemic. However, there is also evidence of increased entrepreneurial motivation and reinforced dedication to their firms. To address the difficulties presented by the pandemic, these women have adopted a range of tactics, including implementation of hygiene protocols and cost-cutting measures, while also embracing digital technology solutions to a greater extent. This study, conducted during the COVID-19 pandemic, is unique because it focuses on female entrepreneurs’ entrepreneurial motivation. This study is the first attempt to explore the entrepreneurial motivations of female entrepreneurs in different types of entrepreneurship. This study provides a new perspective for researchers in this field by synthesizing existing approaches with a hermeneutic and comparative perspective. This research significantly contributes to the realm of entrepreneurship by conducting an interpretive investigation of how the pandemic has affected female entrepreneurs’ motivation and adaptive strategies. The results highlight the ability of these women to recover quickly and adjust to new circumstances, providing a vital understanding of how gender, entrepreneurship, and crisis response interact.